TEACHING ENGLISH USING CLT TO THE FOURTH YEAR STUDENT OF SD N 1 PEGONGSORAN PEMALANG - Wijayanti, Susi Eris (2011)
The study aims to describe the technique of CLT, the procedures of CLT, the objectives of CLT, the teaching materials, the role of teacher and the students, The researcher does three ways in collecting the data, namely: observation, interview, and document. The data are field notes that are taken from event, note of interview with the teacher about the techniques used and document to support teaching English. In collecting the data, the writer focuses on the techniques applied in the class especially to the fourth year students. The result of the research shows that, (1) There are two techniques used in teaching English to the fourth year students of SDN 1 Pegongsoran Pemalang, namely: Games and Role Plays. Those techniques are applied to make the students interested in learning English. (2) The procedures are as follows: Presentation of a brief dialog, Question based on the dialog topic and situation, Sampling of the written homework assignment. (3) Objective of CLT to these fourth year student. (4) There are many problems faced by the teacher in teaching English namely: limited vocabulary, wrong in implementing grammar, pronunciation, and motivation. To solve the problems first, the teacher gives a list of difficult words related to the topic. Second, the teacher gives more exercises and explanation one by one. Third, pronunciation, the teacher gives example how to read the word in English correctly and the students repeat and memorize it. Last in, motivation, the teacher motivates the students in order that they are confident to express their idea. (5) The role of teacher and students are actively engaged in negotiating meaning, trying to make students understand even when their knowledge of the target language.